Assessment of abandoned properties in geopolitical conflict zones. Issue 1 (31st August 2021) - Shojaee-Far, Mohsen
Abstract : Purpose: In geopolitical conflict zones, the phenomenon of abandonment often correlates with challenges of legal definitions and ownership status. The abandoned properties in conflict zones share similar characteristics with what is commonly known as a brownfield site. However, due to the nature of geopolitical conflict zones, which is mixed with people and sentiments other than technical challenges, the usual solutions to the brownfield question, cannot provide enough tools to deal with the land management of areas engulfed in conflicts. This paper, therefore, aims to discuss and propose a land-use typology that describes abandoned properties in a geopolitical context. Design/methodology/approach: The proposed land-use typology serves as the main conceptual framework that integrates the sustainable brownfield regeneration approach with social theories of space and place. As an inductive research approach, this conceptual framework brought the fundamental and comparative literature on brownfield regeneration to support the main argument related to the similarities and challenges of the regeneration of abandoned properties in conflict zones. The approach used in this paper addresses the broader consideration of land management in geopolitical contexts and urban conflict zones that considers the relationship of exercise of extreme power over space. Findings: The findings highlight an insufficient understanding of the origin of the property problems in geopolitical conflict zones, especially after a power struggle, producing significant land management issues. In a geopolitical context, urban planners and economists' perspective on definitions of space and place defined by maps, GIS data sets, Excel and other similar tools may not bring any practical or long-term solution to the land management challenges. The study suggests that dealing with abandoned properties and regeneration plans in conflict zones requires identifying and evaluating geo-political, geo-social, geo-economic characteristics of the area before any further action. Practical implications: This paper's findings are of particular interest to decision-makers and conflict stakeholders in geopolitical conflict zones, such as local governments, policymakers and peacekeeping agencies. The findings of this research can clarify and help them have an alternative understanding of the space engulfed in the conflict, other than a technocratic, mapping, GIS, statistical way of understanding and approaches to the complex aspect of a space. Originality/value: This paper's conceptual framework provides a value-added contribution to the literature on land management in conflict zones by taking the reader's attention to the origin of the problems and their associated real estate issues in geopolitical contexts. For the first time, this inductive research proposes a land-use typology that considers the complexity of the interrelationship between land policies, land-use theory, social theories of space and place and the exercise of extreme power over space. This paper produced a concept that is not easily measurable by quantitative nor qualitative approaches.